The night, the music: a cognitive hypothesis - Dottori, Maurício (Revista Vórtex, 2020)
In this article I present a discussion, based on cognitive psychology and on philosophy, about the application of the metaphor “music as play, instead of the metaphor music as language.” In it I try to distinguish what is properly biological in our hearing system from what is cultural, in order to emphasise, firstly, the hypothesis that music represents the creation of a territory of comfort where sounds are placed in places in which, according to the rules of a game, of a cognitive puzzle, they should be a hypothesis that points to music as art; and, secondly, the idea that cognition of music may be understood as an enlarged auditory scene analysis, based on categorisation, rhythmicalization, and recursive schemes of sounds. This makes possible the building of a capacity to judge the rules of the game of music according to their latent potential and to their functionality; and, not least, to judge how well the creator “plays” the game, because in music (distinctly from the language) a conventional relationship with the world is superfluous, the rules are transmitted to those who attend by the very act of playing the game. As the specific context is not cultural, but that of the game itself, the determination of a great move in play does not depends on a class hegemony, but only on Kantian disinterest.